LIPID DISTRIBUTION IN BODY AND SKIN OF FOUR SPECIES OF MARINE FISH. - MATHEW, P T; DEVADASAN, K; VENKATARAMAN, R (Fishery Technology, 2017)
The paper presents results of a study on the analytica~characteristics of lipids from the skin and muscle of fourimportant species of Gujarat coast fishes. Changes in characteristicslike saponification value, iodine value and unsaponifiablematter of these lipids during different months of the year arealso reported.